Who Called Team Europe? The European Union's Development Policy Response During the First Wave of COVID-19 - Aline Burni; Benedikt Erforth; Ina Friesen; Christine Hackenesch; Maximilian Hoegl; Niels Keijzer (The European Journal of Development Research, 2021)
The COVID-19 pandemic is a critical juncture for global development. Under the label of "Team Europe", the EU has sought to mobilize rapid development assistance to support partners in addressing the impacts of the crisis, while promoting joined-up approaches among European actors to assert itself in a changing and competitive geopolitical context. This article assesses how substantive and process-oriented EU development policy norms are reflected in the Union's global COVID-19 response. Focusing on the EU's response during the first wave of the COVID-19 pandemic in the first half of 2020, the article shows that the EU's response to this extraordinary crisis consisted of a deepening of EU integration. In so doing, the EU emphasized process-oriented over substantive norms in its development policy.
Keywords: 330; European Union; Foreign aid; Development policy; Norm diffusion; COVID-19